2012
DOI: 10.1007/s11033-012-1747-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between estrogen receptor alpha c.454-397T>C and c.454-351A>G and ischemic stroke risk: a systematic review and meta-analysis

Abstract: The association between estrogen receptor alpha (ESR1) c.454-397T>C and c.454-351A>G polymorphism and ischemic stroke remains controversial. The aim of this study was to perform a meta-analysis to investigate a more authentic association between c.454-397T>C and c.454-351A>G mutation and ischemic stroke. Systematic searches of electronic databases Embase, PubMed, Web of Science as well as hand-searching of the references of identified articles and the meeting abstracts were performed. Study selection, data abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…The deletion of ERα in knockout mice completely abolishes the protective effects of E 2 , while the protection against ischemic brain injury is totally preserved in the absence of ERβ. This is also supported by a recent metaanalysis showing that patients carrying loss-of-function mutations of ERα receptor have more severe ischemic brain damage stroke patients (Li et al, 2012). This is in line with other results showing that neuroprotection involves attenuation of NADPH oxidase activation and superoxide production via an ERα-mediated nongenomic signaling cascade (Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…The deletion of ERα in knockout mice completely abolishes the protective effects of E 2 , while the protection against ischemic brain injury is totally preserved in the absence of ERβ. This is also supported by a recent metaanalysis showing that patients carrying loss-of-function mutations of ERα receptor have more severe ischemic brain damage stroke patients (Li et al, 2012). This is in line with other results showing that neuroprotection involves attenuation of NADPH oxidase activation and superoxide production via an ERα-mediated nongenomic signaling cascade (Zhang et al, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have reported significant associations between these SNPs and brain-related disorders, including cognitive impairment a d Alzhei er's disease (www.alzgene.org) Ancelin, 2012, Sundermann et al, 2010), as well as cholesterol levels and cardiovascular disease (Li et al, 2012, Rexrode et al, 2007. There is also some evidence that they may be functionally significant (Alonso et al, 2011, Maruyama et al, 2000.…”
Section: Estrogen Receptor Polymorphismsmentioning
confidence: 99%
“…Associations with cardiovascular disease and ischemic stroke have also been reported (Li et al, 2012, Rexrode et al, 2007. To date however, only three studies have investigated potential associations between ESR gene variants and brain volumes, one of which was a study of neonates (Knickmeyer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, early diagnosis and prevention are critical for disease management. Recent studies have shown that estrogen-related genes are associated with a significantly increased risk of CVD (Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%